الدور التربوي والاجتماعي للبرنامج الإشرافي إجازتي من وجهة نظر المشرفين والمشرفات على البرنامج في مدينة الرياض بالمملكة العربية السعودية - الخالدي، نورة بنت سلمان; المقرن، عبدالله بن محمد (دار سمات للدراسات والأبحاث, 2018)
هدف البحث إلى التعرف على دور برنامج "إجازتي" بمساراته المختلفة، في عدد من المجالات والمهارات، ومعرفة المعوقات التي تحد من تحقيق -أهداف البرنامج من وجهة نظر المشرفين والمشرفات على البرنامج. ولتحقيق أهداف البحث استخدم الباحثان المنهج الوصفي، وتكون مجتمع البحث وعينته من جميع المشرفين والمشرفات على برنامج "إجازتي" في مدينة الرياض والبالغ عددهم 471مشرفا ومشرفة، وزعت عليهم استبانة مكونة من 40 عبارة موزعة على خمسة محاور. وأظهرت النتائج أن المشرفين والمشرفات على برنامج "إجازتي" متفقون على الدور التربوي والاجتماعي لبرنامج "إجازتي" في المجالات والمهارات التالية: بناء مهارة الثقة بالنفس، وبناء مهارة التواصل، وتعزيز الاتجاهات الإيجابية للسياحة الوطنية، وتنمية قيم التطوع والمسؤولية المجتمعية، ومهارة اتخاذ القرار، وبناء المهارات الفكرية. كما بينت النتائج أيضا أن أفراد العينة موافقون على وجود ثلاثة معوقات تحد من تحقيق أهداف البرنامج"، وحياديون حول اثنتين من المعوقات. وبناء على نتائج الدراسة، أوصى الباحثان بتعزيز أهداف برنامج "إجازتي" وتوسيعه بشكل أكبر عبر الأندية المختلفة (الجامعية، والتخصصية)، ونشر الوعي بين الطلاب والطالبات برؤية 2030 بالتزامن مع تطوير المهارات والفعاليات، وضرورة الانتقال من البرامج الترفيهية إلى البرامج العلمية والثقافية التعليمية، وتفعيل دور المشرفين والمشرفات وتطويره؛ لتنمية المهارات التي تناولتها هذه الدراسة.
Ministry of Education in Saudi Arabia launched a summer school program under the name: “Ejazati” to provide multiactivity for both male and female students. This research aimed to investigate the role of this program, from the perspective of male and female supervisors. The investigation covered four main areas: building personal skills, building employability skills needed by labor market, increase positive attitudes toward national tourism, developing values related to volunteering and social responsibility, in addition to Identifying obstacles facing the program. To achieve the objectives of this study, descriptive research approach was utilized, and all members of the study’s population were selected (around 471). A survey questionnaire was administrated that includes 40 items, covering five main themes of this study. Most significant results of this study showed that all respondents agreed regarding the importance of the social and educational role of the Ejazati program, in terms of building confidence, developing decision-making skills, improving positive aspects of participants’ personalities, creating social relationships, and strengthening friendships. Program’s supervisors strongly agreed that the program helped participants in identifying historical and cultural landmarks. Consequently, the program does support positive attitude towards national tourism, and increases participants’ sense of citizenship, through recognition of the achievements of their country. The summer program also develops the value of volunteering and social responsibility by spreading a spirit of love and harmony between community and volunteer work. Finally, the study suggested list of recommendations in relation to program’s improvement that are supporting and increasing the benefits of social and educational role of the program.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- المشرفون -- المشرفات -- الدراسات الإجتماعية -- البرامج الإجتماعية -- السعودية -- المجتمع السعودي -- مستخلصات الأبحاث